Treatment Satisfaction in Systemic Lupus Erythematosus: Development of a Patient-Reported Outcome Measure. Issue 2 (March 2017) - Mathias, Susan D.; Berry, Pamela; Pascoe, Katie; de Vries, Jane; Askanase, Anca D.; Colwell, Hilary H.; Chang, David J.
Abstract : Objective: The aim of this study was to develop a patient-reported outcome measure specific for systemic lupus erythematosus (SLE) to assess patient satisfaction with treatment, treatment options, and medical care. Methods: Patients with SLE were recruited from four US rheumatology practices. Concept elicitation interviews identified aspects that patients considered important and relevant regarding satisfaction with treatment and medical care. Concept elicitation interviews and clinical input were used to draft the Lupus Satisfaction Questionnaire (LSQ). A second cohort of patients with SLE participated in combined concept elicitation/cognitive debriefing interviews, after which the LSQ was revised. Results: Fourteen patients completed concept elicitation interviews: 93% were female, 57% were white, and 85% had moderate/severe SLE. Current treatments included hydroxychloroquine (93%), steroids (79%), and belimumab (57%), and 43% were biologic naive. Patients were generally satisfied with their treatment and medical care; however, they were dissatisfied with treatment adverse effects and the number of available treatment options. Cognitive debriefing interviews (n = 8) demonstrated that the LSQ was comprehensive, clear, and relevant; therefore, only minor revisions were made to the questionnaire. The LSQ assesses satisfaction with current SLE treatments (25 items), medical care (11 items), and insurance coverage (3 items). The draft LSQ was evaluated in 195 adults with SLE. Fifty-eight percent of patients reported that they were "somewhat satisfied" with their SLE treatment. Conclusions: The LSQ has been developed to assess treatment satisfaction among patients with SLE. Following further testing to support its validity and reliability, it will provide a useful tool to facilitate assessment of satisfaction with treatments for SLE and help inform treatment decisions.